Effect of Sugar and Juice Concentration on Vitamin C Retention and Organoleptic of Tangerine (Citrus Reticulata) Powder - Ahmad, Ilham; Jassin, Ernawati; Arisandi, Arwini; Mus, Rahmi; Makkulawu, Andi Ridwan (ITScience (Information Technology and Science), 2025)
Converting tangerine juice into powder via sucrose crystallization yields shelf?stable products with appealing flavor and nutrients. We examined the independent and interactive effects of sucrose and juice concentrations on physicochemical properties and consumer acceptance of Citrus reticulata powder. A 3×3 factorial design evaluated sucrose at 45, 55, and 65% and juice at 45, 55, and 65% (three replications). Processing included extraction and filtration, sucrose addition, controlled heating to supersaturation, crystallization during cooling, milling, and sieving. Moisture content, vitamin C (UV–Vis, 245 nm), and hedonic ratings for texture, aroma, color, and taste (nine?point scale; 30 panelists) were measured. ANOVA and Duncan’s Multiple Range Test assessed treatment effects. Moisture was 2.04–3.07% across treatments and did not differ significantly (p=0.924), meeting the SNI specification for powdered beverages (<5%). Vitamin C differed significantly (p=0.006); the 45% sucrose level consistently produced the highest values (?42.9–43.8 mg/100 g). The A1B3 formulation (45% sucrose, 65% juice) combined high vitamin C ( 43.2 mg/100 g) with acceptable moisture (3.07%) and the most preferred sensory profile. Patterns suggest that reducing sucrose limits thermal/Maillard losses of ascorbic acid, while very high sucrose lowers water activity and yields intermediate retention. Overall, sucrose crystallization produced shelf?stable powders with favorable reconstitution, nutritional, and liking properties. A low?sucrose, high?juice formula optimizes the balance of quality attributes, supporting use in instant citrus drinks and functional beverages.